1981
DOI: 10.1021/bi00526a006
|View full text |Cite
|
Sign up to set email alerts
|

Protein-associated deoxyribonucleic acid strand breaks in L1210 cells treated with the deoxyribonucleic acid intercalating agents 4'-(9-acridinylamino)methanesulfon-m-anisidide and adriamycin

Abstract: The DNA intercalating agents 4'-(9-acridinyl-amino) methanesulfon-m-anisidide (m-AMSA) and adriamycin were studied by using filter elution methods to measure DNA single-strand breaks (SSB's), DNA-protein cross-links (DPC's), and double-stranded breaks (DSB's) in mouse leukemia L1210 cells. Both compounds produced SSB's and DPC's at nearly 1:1 ratios. The SSB's and DPC's were shown to be localized with respect to each other; this was inferred from the finding that filter assays based on protein adsorption compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
151
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(161 citation statements)
references
References 36 publications
9
151
1
Order By: Relevance
“…What is worth noting is that other chemicals DNA SSB produced by HO 33342 alone at concentration such as some anticancer agents (e.g., anthracyclines) of 1.5 pg/ml but not significantly with the concentration cause a comparable number of DNA-SSB at equitoxic of 5 pg/ml. concentrations (27).…”
Section: Discussionmentioning
confidence: 99%
“…What is worth noting is that other chemicals DNA SSB produced by HO 33342 alone at concentration such as some anticancer agents (e.g., anthracyclines) of 1.5 pg/ml but not significantly with the concentration cause a comparable number of DNA-SSB at equitoxic of 5 pg/ml. concentrations (27).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in closing, we would like to propose that such aggregation, in addition to the chromatin structural changes described above, may contribute in a concerted way to the apoptotic cell death induced by these drugs. (58,59) Chromatin aggregation (23) may facilitate or promote the DNA fragmentation (68,69) by specific apoptotic endonucleases. Indeed, it has been recently shown that chromatin aggregation precedes oligonucleosomal fractionation (70) and that DNA is supercoiled in apoptotic chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…A number of cytotoxic drugs which were found to have antineoplastic properties have recently been shown to be topoisomerase inhibitors (3,12,15,25,26,31,33). These drugs typically interfere with the breakage-reunion cycles of topoisomerases to produce single-and double-strand DNA breaks.…”
mentioning
confidence: 99%